ACCOMMODATION BUSINESS DEVELOPMENT STRATEGY IN POST PANDEMIC MARITAL TOURISM DETINATIONS (CASE STUDY OF DUTUNGAN ISLAND IN BARRU DISTRICT, SOUTH SULAWESI PROVINCE) - Kurnia, Kurnia (Universitas Hasanuddin, 2023)
The research is aimed at (1) revealing significant influence factors in developing maritime tourism based on tourist characteristics and (2) formulating the strategy of maritime tourism development in Dutungan Island Barru Regency. The method used in this research was quantitative descriptive, using primary data obtained through interviews and questionnaire techniques with related informants and tourists by using Chi-Square analysis with SWOT. The strategy formulation for maritime tourism development is tourism accommodation development with middle-class marketing segments, preserving nature and the seashore clean, broadening the opportunity for business, collaborating with travel bureaus, spreading information and promotion of tourism, making local traditions a tourism attraction, procuring marine tourism transport, training professional tourism agents, and developing local community roles in achieving security.